2018
DOI: 10.1186/s13148-018-0462-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of UHRF1 promotes silencing of tumor suppressor genes and predicts outcome in hepatoblastoma

Abstract: BackgroundHepatoblastoma (HB) is the most common liver tumor of childhood and occurs predominantly within the first 3 years of life. In accordance to its early manifestation, HB has been described to display an extremely low mutation rate. As substitute, epigenetic modifiers seem to play an exceptional role in its tumorigenesis, which holds promise to develop targeted therapies and establish biomarkers for patient risk stratification.ResultsWe examined the role of a newly described protein complex consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
(45 reference statements)
2
41
0
1
Order By: Relevance
“…Increased expression of DNMT1, DNMT3A and UHRF1 proteins can cause hypermethylation of the gene promoter region, which may play a key role in the hypermethylation of the promoter region of HB TSGs [74]. Other experiments have also confirmed that UHRF1 expression in HB is increased [75], TSG promoter region methylation is increased, and gene expression is decreased. After knockout of UHRF1, TSG was re-expressed, indicating that UHRF1 is a key protein promoting hypermethylation and inhibiting the expression of TSGs, which can lead to hypermethylation of TSGs and inhibit expression.…”
Section: Abnormalities Of Dna Methylation Regulatory Enzymes In Hbmentioning
confidence: 90%
See 1 more Smart Citation
“…Increased expression of DNMT1, DNMT3A and UHRF1 proteins can cause hypermethylation of the gene promoter region, which may play a key role in the hypermethylation of the promoter region of HB TSGs [74]. Other experiments have also confirmed that UHRF1 expression in HB is increased [75], TSG promoter region methylation is increased, and gene expression is decreased. After knockout of UHRF1, TSG was re-expressed, indicating that UHRF1 is a key protein promoting hypermethylation and inhibiting the expression of TSGs, which can lead to hypermethylation of TSGs and inhibit expression.…”
Section: Abnormalities Of Dna Methylation Regulatory Enzymes In Hbmentioning
confidence: 90%
“…According to the literature reports, the RASSF1A, UHRF1, MT1G, and NDRG2 promoter regions are hypermethylated. The degree of methylation is related to postoperative recurrence and distant metastasis and can be used as a marker for diagnosis and prognosis [31,41,54,73,85].…”
Section: Diagnosis and Treatment Of Dna Methylation Aberrationsmentioning
confidence: 99%
“…USP7 directly regulates DNMTl's DNA-binding ability [15,54], but there is disagreement over whether USP7 directly binds and stabilizes DNMT1 [55,56]. This may suggest that that UHRF1, USP7, and DNMT1 operate as an E3 ligase-USP7-target complex that forms at promoters of known tumor suppressors and represses them by increased DNA methylation and histone modifications [57]. Recently, it was also shown that M-phase CDK1-CCNB phosphorylates UHRF1's USP7 interacting domain, thus decreasing its interaction with USP7 and its stability in M phase [58], suggesting cell cycle control of methylation through USP7.…”
Section: Top To Bottom: Usp7 As a Regulator At The Epigenetic And Tramentioning
confidence: 99%
“…The result confirmed the certainty of functional driver genes in point zonated metabolic enzymes, which showed the consistency of hypomethylation and overexpression patterns ( 15 ). Another integrative analysis was performed to focus on an epigenetically regulated protein complex including E3 ubiquitin-like containing PHD and RING finger domain 1 (UHRF1) involved in DNA methylation and regulation on promoter regions in human hepatoblastoma (HB) cell lines – HUH6, HepT1, and HepG2 ( 106 ). Through integrative analysis of bisulfite-treated DNA pyrosequencing and RNA-Seq, epigenetic functions of UHRF1 were validated by finding HB-specific transcriptional changes on HHIP , IGFBP3 , and SFRP1 which were highly expressed with decreased methylation levels on UHRF1 depleted HB model ( 106 ).…”
Section: Integrative Analysis With Transcriptome and Other Sequencingmentioning
confidence: 99%
“…Through integrative analysis of bisulfite-treated DNA pyrosequencing and RNA-Seq, epigenetic functions of UHRF1 were validated by finding HB-specific transcriptional changes on HHIP , IGFBP3 , and SFRP1 which were highly expressed with decreased methylation levels on UHRF1 depleted HB model ( 106 ). In addition, the overexpression of UHRF1 was shown in patients with poor disease status ( 106 ). As a result, the role of UHRF1 was identified as a critical epigenetic gene in HB and UHRF1 was suggested as a prognostic biomarker in HB ( 106 ).…”
Section: Integrative Analysis With Transcriptome and Other Sequencingmentioning
confidence: 99%